Modelling of shallow foundations for offshore structures - Houlsby, G (2003)
The numerical modeling of shallow foundations on clay for the offshore industry was discussed. The new models combined with structural analyses predict the behavior of the entire structure system under dynamic loading conditions. The principle of the models was based on work hardening plasticity theory and caissons for offshore wind turbine applications. The new model comes from the emerging offshore wind power sector, in which suction caissons were considered as an alternative to piled foundations.